The Islamic State in Muhammad Iqbal’s Thought: Integrating Monotheism, Islamic Ethics, and Modernity - Nurfazillah, Nurfazillah (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
The idea of establishing an Islamic state has long attracted the attention of Muslim intellectuals, including Muhammad Iqbal. His proposal for the creation of a separate state for Indian Muslims was inseparable from the socio-political conditions of the time, in which Muslims lived under the dominant influence of Hindu nationalism. This article aims to describe and analyze the concept of the Islamic state from Muhammad Iqbal’s perspective. Employing a qualitative methodology, the study is based on literature review and historical analysis. The findings indicate that Iqbal’s vision of an Islamic state is not theocratic in nature, but rather grounded in Islamic spiritual and ethical values. Such a state, according to Iqbal, must be guided by the Qur’an and Sunnah, with divine law as the highest source of authority and the head of state serving as its executor. Iqbal advocates for a republican form of government, in which the state functions as a vehicle to realize the ideals of tawhid (monotheism), social justice, and individual freedom. His concept seeks to harmonize religion with modernity, and to integrate democracy with Islamic ethical foundations. The article concludes that Iqbal’s political thought contributed significantly to the founding of Pakistan, and offers a relevant model for other Muslim-majority nations striving to implement Islamic principles in state governance, with the ultimate aim of building a just society rooted in the Qur’an and Sunnah.